Pengaruh Social Media Marketing Akun Instagram @revassutamamedika Terhadap Citra Perusahaan PT Revass Utama Medika - Muthia Malihah Raniah Halim; David Rizar Nugroho; Ika Yuliasari (Jurnal Komunikasi Nusantara, 2025)
In the digital era, Instagram has become one of the most influential platforms in shaping public perceptions of a company. PT Revass Utama Medika uses Instagram as a digital communication medium to deliver corporate information and strengthen its positive image. This study aims to examine the influence of Social Media Marketing on the Instagram account @revassutamamedika on the corporate image of PT Revass Utama Medika. The research employed a quantitative approach involving 100 respondents who follow the account. The study applies Social Media Marketing indicators—entertainment, interaction, trendiness, customization, and forward information—along with corporate image indicators consisting of personality, reputation, value, and corporate identity. The results show that Social Media Marketing on the @revassutamamedika account has a positive and significant influence on the corporate image of PT Revass Utama Medika, contributing 78.1%. Regression analysis indicates a positive, unidirectional relationship between the two variables, meaning that better implementation of Social Media Marketing strategies leads to a stronger corporate image in the eyes of the public. These findings demonstrate that improving content quality, increasing interaction with followers, and maintaining consistent information delivery play important roles in strengthening the audience’s positive perception of PT Revass Utama Medika. Abstrak Di era digital, Instagram menjadi salah satu platform yang berpengaruh dalam membentuk persepsi publik terhadap perusahaan. PT Revass Utama Medika memanfaatkan Instagram sebagai media komunikasi digital untuk menyampaikan informasi perusahaan dan memperkuat citra positif. Penelitian ini bertujuan untuk mengetahui pengaruh Social Media Marketing pada akun Instagram @revassutamamedika terhadap citra perusahaan PT Revass Utama Medika. Penelitian menggunakan metode kuantitatif melalui penyebaran kuesioner kepada 100 pengikut aktif. Indikator Social Media Marketing meliputi entertainment, interaction, trendiness, customization, dan forward information, sedangkan citra perusahaan diukur melalui personality, reputation, value, dan corporate identity. Hasil penelitian menunjukkan bahwa Social Media Marketing berpengaruh positif dan signifikan terhadap citra perusahaan dengan kontribusi sebesar 78,1%. Analisis regresi juga menunjukkan adanya hubungan yang positif dan searah antara kedua variabel, yang berarti semakin baik penerapan strategi pemasaran melalui Instagram, semakin kuat citra perusahaan terbentuk di mata publik. Temuan ini menunjukkan bahwa kualitas konten, interaksi dengan audiens, dan konsistensi penyampaian informasi berperan penting dalam memperkuat persepsi positif terhadap PT Revass Utama Medika.